Electron-positron pair photo-production with radiation of a photon in magnetic field at nonresonant regime - Fomin, P.I.; Kholodov, R.I. (Вопросы атомной науки и техники, 2012)
Theoretical investigations of quantum electrodynamic processes in strong magnetic field are carried out. Such the processes may occur between colliding heavy ions. Magnetic fields of the nuclei are added and electric fields of nuclei mutually compensate one another in that region. The electron-positron pair production by a photon in the case when one additional photon is emitted in external magnetic field under nonresonant condition has been investigated. Kinematics of the process and the resonance conditions in approximation of strong magnetic field and weakly excited electron (positron) states (ultra-quantum approximation) have been studied. The resonant conditions have the place, when the photon energy is close to the splitting between Landau levels. The differential probability of nonresonant process has been obtained. The probability of the process is three order of magnitude less the resonant case. Проводятся теоретические исследования квантово-электродинамических процессов в сильном магнитном поле. Такие процессы могут происходить между сталкивающимися тяжелыми ионами. В этой области магнитные поля ядер складываются, а электрические поля взаимно компенсируются. Исследуется процесс рождения электрон-позитронной пары фотоном в случае, когда излучается один дополнительный фотон во внешнем магнитном поле при нерезонансных условиях. Изучаются кинематика процесса и условия резонанса в приближении сильного магнитного поля и слабо возбужденных состояний электронов (позитронов). Резонансные условия имеют место, когда энергия фотона близка к расстоянию между уровнями Ландау. Получена дифференциальная вероятность нерезонансного процесса в единицу времени. Вероятность такого процесса на три порядка меньше резонансного случая. Проводяться теоретичні дослідження квантово-електродинамічних процесів в сильному магнітному полі. Такі процеси можуть відбуватися при зіткненні важких іонів. В області між ними магнітні поля ядер складаються, а електричні поля взаємно компенсуються. Досліджується процес народження електрон-позитронної пари фотоном у випадку, коли випромінюється один додатковий фотон в зовнішньому магнітному полі при нерезонансних умовах. Вивчаються кінематика процесу і умови резонансу в наближенні сильного магнітного поля і слабо збуджених станів електронів (позитронів). Резонансні умови мають місце, коли енергія фотона близька до відстані між рівнями Ландау. Знайдено диференційну ймовірність нерезонансного процесу в одиницю часу. Ймовірність такого процесу на три порядки менша за резонансний випадок.